The Continuation of Business Activities According to Polish and International Regulations - Szczepankiewicz, Elżbieta Izabela (Studia Oeconomica Posnaniensia, 2013)
The basic principle on which a financial statement is drawn up is the continuation of business activities. This article discusses issues related to the identification and classification of financial and non-financial events and conditions that may indicate a threat to the continuation of business on the basis of national and international regulations concerning accounting and financial audits. The research methods adopted in the study include a literature analysis, a review of legislative acts on international accounting standards as well as international standards of auditing, including deductive reasoning.